Comparative evaluation of laparoscopic splenectomy versus open splenectomy - Okhrimenko, H. I.; Holovko, M. H.; Hrushka, V. A.; Haidarzhi, Ye. I.; Pоdluzhnyi O. O. (Zaporozhye Medical Journal, 2018)
The aim of research: to study the short-term treatment results in patients with blood diseases, portal hypertension, pathology of the spleen who underwent laparoscopic splenectomy based on the surgical indications in comparison with the treatment results in the patients who underwent open surgery. Materials and methods. The results of treatment for 50 patients with blood diseases, portal hypertension and pathology of the spleen were analyzed. The main group consisted of 15 patients who underwent laparoscopic splenectomy. The control group comprised 35 patients who underwent open surgery. Results. The spleen sizes detected on CT in the control group patients were significantly larger in comparison with the spleen sizes in the main group patients. Profuse bleeding as an intraoperative complication was observed in 2 (13.33 %) patients of the main group that was the reason for a conversion. There were no postoperative complications and fatal cases in contrast to the control group. Conclusions. It has been established that laparoscopic splenectomy should be performed for moderate splenomegaly up to20 cm. To prevent a profuse bleeding during this operation the meticulous hemostasis is needed indefinitely.